Lifelong learning to labour: apprenticeship, masculinity and communities of practice - Parker, Andrew (British Educational Research Journal, 2006)
This article presents an analysis of gender identity within the context of lifelong learning. Constructed specifically around individual experiences of occupational apprenticeship in English professional football, it draws on a re-reading of data collected in the early 1990s to depict the way in which a group of young men were socialised into their new-found occupational culture and how their identities were shaped by the heavily gendered routines of workplace practice. Framing apprenticeship as a holistic 'learning' experience, the article looks at how the legitimate peripheral participation of trainees in an established community of practice facilitated their adaptation to and assimilation of various skills, procedures and institutional norms via informal learning processes. Set against the historical development of apprenticeship in England, the article uses qualitative research findings to determine the extent to which apprenticeship within professional sport might facilitate the reproduction of stereotypical gender norms and values.
Keywords: apprentissage; apprentissage tout au long de la vie; contexte d'apprentissage; genre; processus d'apprentissage; utilisation des recherches; éducation prioritaire